Post-traumatic urbanism to assess the impacts of COVID-19 in cities - Acosta Schnell, Sabrine (2021)
The term post-traumatic urbanism is addressed as the main subject of this essay, term commonly discussed in the context of various conflicts and disasters (natural or man-made). I propose as the main objective to reflect on this concept and its possible contributions as a tool for analyzing the process of recovery and resilience of cities in the face of the global COVID-19 pandemic. Regarding the methodology, a critical and not extensive bibliographic review was used. It is selective with two main authors: the architect and researcher Adrian Lahoud who discusses the concept of the effect of trauma in urban planning and, later, the contributions of the French philosopher and sociologist, Edgar Morin, on the subject of virtuous circularity. The central points of the reflection suggest to avoid proposing a solution or an urban project ina generic way to all cities worldwide, in the post-pandemic context. The results indicate, that despite the patterns identified as common reactions to traumatic events, it is important to promote an improved evolution of urban dynamics, far from returning to the same pre-trauma state. As final conclusions, it is highlighted the importance of the specificities of each case study when evaluating the resilience of each urban location. In times of change and extreme situations, as with COVID-19, uncertainty has to catapult research that supports decision-making and with new study niches that provide knowledge to the various urban actors.